RESTORATIVE JUSTICE DALAM PENEGAKAN HUKUM TINDAK PIDANA PENYALAHGUNAAN NARKOBA DI KECAMATAN SENYERANG TANJUNG JABUNG BARAT - Patoni Patoni; Ruslan Abdul Gani; Rasito Rasito (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to examine the law enforcement of criminal acts in Indonesia, as a country law, of course enforcement law that doesn't take sides has set in Constitution 1945 Constitution Article 27 paragraph (1) of the 1945 Constitution where everyone is treated same in front law . Restorative justice is an alternative law enforcement approach that prioritizes solidarity, custom and culture, as regulated in the decision letter of the Supreme Court of the Republic of Indonesia concerning application of restorative justice. This study resulted in four things, namely: 1. General description of drug abuse crimes in Senyerang District 2. Efforts made by the Senyerang Pengabuan Police against drug abuse by applying the concept justice restorative justice, 3. Forms of restorative justice on drug abuse 4. MUI decree against eating and drinking containing alcohol/ethanol. The conclusion of the study is that drug abuse is a victim of crime, drug law enforcement can only be carried out with prevention without punishment and rehabilitation methods which are the implementation of restorative justice, drugs can be interpreted as khomar and the law is haram.